2015
DOI: 10.3109/10717544.2015.1124474
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy of drug transdermal delivery by electro-phonophoresis in treating tuberculous lymphadenitis

Abstract: Electro-phonophoresis (EP) has been used in various clinical fields. The objective of present study is to evaluate the skin permeability of isoniazid (INH) and rifampicin (RIF) in patients with tuberculous lymphadenitis with the aid of EP to validate the clinical applications of this transdermal delivery system for the treatment of superficial extrapulmonary tuberculosis. INH and RIF solutions were delivered transdermally, with or without EP, in the surrounding tissue of the lesion for 0.5 h. Local pyogenic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…However, these results are a little different from that of our previous study, in which we examined whether EP can effectively increase the penetration of the INH and RIF through skin in tuberculous lymphadenitis patients and verified that application of EP significantly enhances both INH and RIF penetration through skin (Chen et al, 2016). Because of the difficulty of obtaining the pyogenic fluids, the pharmacokinetic studies of the change of drug concentrations in pyogenic fluids over an extended period of time and the optimal ultrasonic intensity and dosage were not addressed in previous study.…”
Section: Discussioncontrasting
confidence: 97%
“…However, these results are a little different from that of our previous study, in which we examined whether EP can effectively increase the penetration of the INH and RIF through skin in tuberculous lymphadenitis patients and verified that application of EP significantly enhances both INH and RIF penetration through skin (Chen et al, 2016). Because of the difficulty of obtaining the pyogenic fluids, the pharmacokinetic studies of the change of drug concentrations in pyogenic fluids over an extended period of time and the optimal ultrasonic intensity and dosage were not addressed in previous study.…”
Section: Discussioncontrasting
confidence: 97%
“…These values were significantly (p ˂ 0.05) higher than previously reported, and were high enough to kill skin cells and promote RIF values in the circulation substantially higher than the minimum inhibitory concentration (0.25 µg/mL) of RIF. 41 These results showed that RIF-loaded nanoemulsions may be promising formulations for transdermal delivery of RIF.…”
Section: Ex Vivo Permeation and Drug Deposition Studiesmentioning
confidence: 84%
“…Drug precipitation from the o/w nanoemulsion in the skin strata was not of concern because RIF is lipophilic. 41 In contrast, isoniazid, which is hydrophilic, has been used for sustained topical delivery, which may result from precipitation in lipophilic skin regions. 41 The desirability function was used to validate the optimization parameters and to specify constraints for responses.…”
Section: Optimization Of the Nanoemulsionmentioning
confidence: 99%
See 2 more Smart Citations